Güneş aktivitelerinin Kuzey Atlantik salınımı ve arktik salınım üzerindeki etkileri ile bunların yağış ve sıcaklık değerleri bakımından Türkiye'den örnekler ile değerlendirilmesi - Bozyurt, Okan (Sosyal Bilimler Enstitüsü, 2022)
Earth Climate System has a very complex structure. This very complex structure indicates the character of a sensitive structure on the one hand. Solar activities are the most important factor of that system.In this study, sunspots and temperature fluctiations have been compared in former ages or periods. In addition to this, the trends of solar activities have been tried to be determined by analysing the conditions of solar activities fort the last period of 60 years. General trend goes to the decreases in solar activities, more and more. Particularly, the year of 2008 has been recorded as a deepest minimum in terms of solar activities fort the last period of 50 years.Although solar activities are very important factor which determine Earth Climate System, atmospheric oscillations which are from ocean and atmosphere system, are also important components in climate system. Recently, North Atlantic Oscillations have been a popular issue or matter as well as ENSO (El Nino-La Nina cycle) among climatologists. Because some atmospheric events can not be explained only ENSO (El Nino-La Nina cycle). While Europe continent is affected by wetter and warmer conditions, Mediterranean Basin which also contains Turkey, is affected by colder and drier conditions. In fact these climatic characters are more common in winter seasons so winter conditions are very important for North atlantic oscillation.Apart from this, in some winter seasons in Europe and Mediterranean Basin colder conditions as well as wetter conditions are important questions for climatologists. Because these climatic conditions can not be explained only by North Atlantic Oscillations. So Arctic Oscillation started to gain importance.According to researches, while Mediterranean Basin indicates, generally, colder and drier conditions, Europe indicates wetter and warmer conditions in winter seasons in pozitive phase of North Atlantik Oscillation and Arctic Oscillation. On the other hand, while mediterranean Basin indicates wetter and warmer conditions, Europe ...